Physician-user interaction and users' perceived service quality: evidence from Chinese mobile healthcare consultation. Issue 5 (30th June 2020) - Tan, Hongying; Yan, Mengling
Abstract : Purpose: The significance of physician-user interaction has been widely acknowledged in offline and online healthcare consultation. However, limited attempts have been made to explore the influence of physician-user interaction on users' perceived service quality (PSQ) in the mobile context. Based on the literature on physician-user interaction and media synchronicity theory, this study proposes a theoretical model where the interactive factors common across the offline, online and mobile context, i.e. physicians' informational support and emotional support, the interactive factors unique in the mobile context, i.e. physicians' response speed and voice service, and the interaction between the two categories of interactive factors predict users' PSQ in mobile consultation. Design/methodology/approach: This study collects consultation records between 25, 225 users and 738 physicians from a leading Chinese mobile consultation application, and employs linear regression to verify the proposed theoretical model. Findings: Physicians' informational, emotional support, response speed and voice service are found to have significant positive impacts on users' PSQ. Besides, physicians' response speed strengthens the positive impacts of physicians' informational and emotional support on users' PSQ, while physicians' voice service weakens the positive link between physicians' informational support on users' PSQ. Originality/value: This study contributes to the antecedents for users' PSQ in mobile consultation by identifying unique interactive factors in the mobile context, and highlighting the individual and interaction effects of different physician-user interactive factors. Besides, this study employs novel methods, which leverages text classification and text pattern recognition to more accurately depict physicians' online behaviors based on objective communication records.